Effect of Iodine Solution Treatment With Different Dosage And Exposed Duration to Metamorphosis Rate and Survival of Bullfrog Tadpoles (Rana Catesbeiana Shaw) - Lutviyana Rahman; Nia Kurniawan (University of Brawijaya, 2014)
Objective of this research was to know the role of iodine with different doses and exposed duration to against the rate metamorphosis and survival of bullfrog’s tadpoles. Methods on this research are acclimatization of bullfrog’s tadpoles, given iodine solution such as doses 3 mg/L, 4 mg/L, 5 mg/L and control (0 mg/L). It observe on 7th, 14th and 21st day of to exposed. The parameters that observed there are tadpole metamorphosis, survival rate and water quality. Data were analyzed using two-way ANOVA and continued with Tukey test. The results showed that water quality on a good category for bullfrog of natural environment. ANOVA for bullfrog metamorphosis rate obtained at p-value (< 0.05). Duration of exposed and doses are significantly influent to against bullfrog’s tadpoles metamorphosis. Although survival rate of bullfrog tadpoles was decline at 21th duration and survival rate of bullfrog’s lowest in doses 5 mg/L. The conclusion is treatment of iodine solution at given in the medium of life bullfrog’s tadpoles and exposed duration of iodine can increase the rate of metamorphosis, but inclined decrease survival rate of bullfrog’s tadpoles. Iodine solution most effect on the rate metamorphosis bullfrog’s tadpoles on exposed 7th, 14th and 21st days on the doses of iodine solution 5 mg/L (5 ppm), while survival rate of bullfrog’s tadpoles is the highest on treatment control (0 mg/L).